Intimate Partner Violence: A New Cognitive, Interpersonal and Motivational Framework for the Rehabilitation of Perpetrators in Portugal - Capinha, Marta (International journal of offender therapy and comparative criminology, 2025)
Intimate partner violence (IPV) has been targeted as a significant concern worldwide, but evidence for the efficacy of perpetrators’ interventions is not undisputable. This article briefly summarizes the evidence about perpetrators’ intervention efficacy, factors associated with recidivism, and evidence-based recommendations, before outlining the assumptions of a new community-delivered intervention aiming to rehabilitate IPV perpetrators: the CONTIGO Program. This program uses an innovative framework, focused on early maladaptive schemas, and combining cognitive, interpersonal, and motivational interview principles. The features of this intervention are discussed, and exploratory results regarding drop-out rates (8%) and recidivism (15.4%) in a sample of 162 court-mandated males are exposed. The detailed presentation of the CONTIGO Program and its intervention model represents a novel contribution that is sorely lacking in the IPV literature and could foster further research and debate about what can be done to effectively intervene with IPV perpetrators.